THE ROLE OF A FAMILY IN CONTROLING ENVIRONMENTAL INFLUENCE IN CHILDREN - Novi Widiastuti; Sri Hartini; Anita Rakhman (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
Home is the first school for children. This means that parents are the first teachers for children. Parental involvement can help teachers build knowledge as well as instill attitudes towards children in instilling discipline and reducing life problems and raising awareness for learning. The success or failure of a person in learning is due to several factors that influence the achievement of learning outcomes, which come from within the person who is learning and some are from outside himself. One external factor is family. This study aims to determine the function of the family in overcoming the influence of the environment of early childhood on Jl. Grandparent Prosecutor, Cipadung, Cibiru Sub-District, Bandung City. Formulation of this research problem How is the function of the family in protecting early childhood from the influence of the community environment? The results of the study concluded that the role of the family in early childhood social development can be successful if parents as the main members of the family can provide good service to early childhood to help development needs and foster children's confidence.